A comprehensive review on utilization of waste materials in wood plastic composite - Ros Azlinawati, Ramli (Elsevier, 2024)
Wood plastic composite (WPC) is a composite material that consists of a matrix phase of plastic and wood as its reinforcement. The transition from virgin plastic (VP) to recycled plastic (RP) has gained popularity due to the increasing amount of plastic waste generated. Increasing in global demand for timber has resulted in a worldwide shortage of forests and rise environmental awareness. The use of RP and natural fiber (NF) in WPC manufacturing is an effective way to reduce environmental impact of conventional WPC, while enhancing the eco-efficiency of the products. This article reviews the basic principle such as definitions and classifications of WPC from plastics waste and lignocellulosic fiber (LCF). Raw materials, additives and resulting properties of the WPCs are briefly discussed. In addition, recent study of WPC is highlighted. Finally, important conclusions and outlook have been mentioned at the end of this article.